The microenvironment in hepatocyte regeneration and function in rats with advanced cirrhosis - Liping Liu; Govardhana Rao Yannam; Taichiro Nishikawa; Toshiyuki Yamamoto; Hesham Basma; Ryotaro Ito; Masaki Nagaya; Joyeeta Dutta‐Moscato; Donna B. Stolz; Fenghai Duan; Klaus H. Kaestner; Yoram Vodovotz; et al. (2011)
In advanced cirrhosis, impaired function is caused by intrinsic damage to the native liver cells and from the abnormal microenvironment in which the cells reside. The extent to which each plays a role in liver failure and regeneration is unknown. To examine this issue, hepatocytes from cirrhotic and age-matched control rats were isolated, characterized, and transplanted into the livers of noncirrhotic hosts whose livers permit extensive repopulation with donor cells. Primary hepatocytes derived from livers with advanced cirrhosis and compensated function maintained metabolic activity and the ability to secrete liver-specific proteins, whereas hepatocytes derived from cirrhotic livers with decompensated function failed to maintain metabolic or secretory activity. Telomere studies and transcriptomic analysis of hepatocytes recovered from progressively worsening cirrhotic livers suggest that hepatocytes from irreversibly failing livers show signs of replicative senescence and express genes that simultaneously drive both proliferation and apoptosis, with a later effect on metabolism, all under the control of a central cluster of regulatory genes, including nuclear factor κB and hepatocyte nuclear factor 4α. Cells from cirrhotic and control livers engrafted equally well, but those from animals with cirrhosis and failing livers showed little initial evidence of proliferative capacity or function. Both, however, recovered more than 2 months after transplantation, indicating that either mature hepatocytes or a subpopulation of adult stem cells are capable of full recovery in severe cirrhosis. Transplantation studies indicate that the state of the host microenvironment is critical to the regenerative potential of hepatocytes, and that a change in the extracellular matrix can lead to regeneration and restoration of function by cells derived from livers with end-stage organ failure.